A New Organic Acid Derived from the Stem of Alsophila spinulosa (Hook.) Tryo - Wu, San-Lin; Li, Shu-Hua; Liu, Fang (Asian Journal of Chemistry, 2012)
A new organic acid, named 3-acetyl-4-O-b-D-glucopyranoside caffeic acid has been isolated from the Chinese medicinal herb Alsophila spinulosa (Hook.) Tryo. The structure was charaterized by 1D and 2D NMR, 13C NMR, ESIMS, HRESIMS spectra.